Legal Politics of Restricting Access to Online Gambling in Fiqh Siyasah and Saddu adz-Dzariah Perspectives - Syarifuddin Syarifuddin; Elvi Soeradji; Imam Alfiannoor; Suradilaga, Aris Sunandar; Mowafg Abrahem Masuwd (Nurani: jurnal kajian syari'ah dan masyarakat, 2025)
This research examines how online gambling poses serious threats to the stability and cohesion of family life. Regardless of the individuals involved, its influence often results in psychological harm such as addiction, job loss, family breakdown, indebtedness, and even criminal behavior. These issues call for in-depth examination through normative legal methods combined with real-time case studies, highlighting online gambling as a current and pressing legal issue. This study employs the framework of fiqh siyasah alongside the principle of saddu adz-dzari'ah to guide its analysis. From a legal-political perspective, some argue that Indonesia could legalize online gambling to increase state revenue through entertainment taxes. However, this perspective contradicts the principles of siyasah maaliyah within fiqh siyasah, which emphasizes that state income should align with both worldly and spiritual welfare. Accordingly, siyasah dusturiyah underscores the importance of preventing the potential harms (mafsadat) associated with online gambling, in line with the principle of saddu adz-dzari'ah, to protect the integrity of families in Indonesia.